2005
DOI: 10.1111/j.1745-7254.2005.00013.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pravastatin on impaired endothelium-dependent relaxation induced by lysophosphatidylcholine in rat aorta1

Abstract: Aim: To investigate the effects of pravastatin, a potent 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor, on impaired endothelium-dependent relaxation induced by lysophosphatidylcholine (LPC), the major component of oxidized low-density lipoprotein, in rat thoracic aorta. Methods: Both the endothelium-dependent relaxation response to acetylcholine and the endotheliumindependent relaxation response to sodium nitroprusside of aortic rings were measured by recording isometric tension after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In these conditions, LysoPtdCho induced a decrease in the stimulating effect of histamine on eNOS activity and a concomitant decrease in Ser 1177 eNOS phosphorylation. This result is in agreement with the decreased endothelial release of NO by LysoPtdCho as reported in the literature [26,27]. Several mechanisms have been proposed to explain the effect of LysoPtdCho including a decrease of arginine availability due to an inactivation of the arginine transporter [28], an increased production of asymmetric dimethyl arginine (ADMA), an endogenous eNOS inhibitor [29], or still a decrease in eNOS expression [30].…”
Section: Discussionsupporting
confidence: 93%
“…In these conditions, LysoPtdCho induced a decrease in the stimulating effect of histamine on eNOS activity and a concomitant decrease in Ser 1177 eNOS phosphorylation. This result is in agreement with the decreased endothelial release of NO by LysoPtdCho as reported in the literature [26,27]. Several mechanisms have been proposed to explain the effect of LysoPtdCho including a decrease of arginine availability due to an inactivation of the arginine transporter [28], an increased production of asymmetric dimethyl arginine (ADMA), an endogenous eNOS inhibitor [29], or still a decrease in eNOS expression [30].…”
Section: Discussionsupporting
confidence: 93%
“…38 Moreover, the enhancement of relaxation of rat aorta to acetylcholine after atorvastatin treatment was eliminated in the presence of SOD, suggesting that reduction in superoxide was the major mechanism for the enhanced relaxation response to acetylcholine. 38 Similar protective effects against oxidative stress have been suggested for both acute 29 and chronic in-vivo 39 and in-vitro 40 protection by statins against low-density lipoprotein-induced endothelial dysfunction in rat aorta.…”
Section: Mechanism Of Pravastatin's Effects On Responses In Small Vesmentioning
confidence: 77%
“…Influence of Superoxide on the Effect of Pravastatin Because pravastatin could potentially limit superoxide levels 28, 29 and thereby inhibit the degradation of NO to peroxynitrite, pravastatin's effect on phenylephrine responses was assessed in the presence of maximal superoxide scavenging with polyethylene glycol-superoxide dismutase (PEG-SOD). The concentration of PEG-SOD required for maximal superoxide scavenging was determined in preliminary experiments in a cell-free system, using superoxide generation by hypoxanthine-xanthine oxidase and measurement via lucigenin-derived chemiluminescence assessed using a Picolite-luminometer (Packard Instruments, CT, USA).…”
Section: Study Protocolsmentioning
confidence: 99%
“…The patients who used ACEIs/ARBs, or statins had better FMD values than the patients who did not use ACEIs/ARBs or statins ( Table 2 ). Previous studies have suggested that statins can upregulate endothelial nitric oxide synthase, thereby improving endothelial-dependent vasodilatation of rat aorta [ 31 , 32 ]. The interaction between angiotensin II and angiotensin II receptor type I may increase reactive oxygen species production, further attenuating the nitric oxide and bradykinin production.…”
Section: Discussionmentioning
confidence: 99%